Differential Cytokine Utilization and Tissue Tropism Results in Distinct Repopulation Kinetics of Naïve vs. Memory T Cells in Mice - Kim, Hye Kyung; Chung, Hyunsoo; Kwon, Juntae; Castro, Ehydel; Johns, Christopher; Hawk, Nga V.; Hwang, SuJin; Park, Jung-Hyun; Gress, Ronald E. (Frontiers in Immunology, 2019)
Naïve and memory T cells co-exist in the peripheral T cell pool, but the cellular mechanisms that maintain the balance and homeostasis of these two populations remain mostly unclear. To address this question, here, we assessed homeostatic proliferation and repopulation kinetics of adoptively transferred naïve and memory T cells in lymphopenic host mice. We identified distinct kinetics of proliferation and tissue-distribution between naïve and memory donor T cells, which resulted in the occupancy of the peripheral T cell pool by mostly naïve-origin T cells in short term (< 1 week), but, in a dramatic reversal, by mostly memory-origin T cells in long term (>4 weeks). To explain this finding, we assessed utilization of the homeostatic cytokines IL-7 and IL-15 by naïve and memory T cells. We found different efficiencies of IL-7 signaling between naïve and memory T cells, where memory T cells expressed larger amounts of IL-7R but were significantly less efficient in activation of STAT5 that is downstream of IL-7 signaling. Nonetheless, memory T cells were superior in long-term repopulation of the peripheral T cell pool, presumably, because they preferentially migrated into non-lymphoid tissues upon adoptive transfer and then additionally utilized tissue IL-15 for rapid expansion. Consequently, co-utilization of IL-7 and IL-15 provides memory T cells a long-term survival advantage. We consider this mechanism important, as it permits the memory T cell population to be maintained in face of constant influx of naïve T cells to the peripheral T cell pool and under competing conditions for survival cytokines.